The thirteenth juror - Nir, Esther (The British journal of criminology, 2019)
Judges presiding over jury trials are tasked with imposing sentence on convicted defendants, even though they play little role in deciding guilt. When judges agree with the jury’s verdict, this arrangement is unproblematic; when they do not, judges are placed in a challenging predicament. Although they may take the extraordinary step of overriding the jury’s decision, this is a rare option reserved for highly exceptional circumstances. Based on interviews with 41 US judges, this study investigates whether judges, consciously or otherwise, employ more subtle means of correcting perceived guilt-phase injustices by calibrating sentence severity according to their confidence in the jury’s verdict. Judges’ rationales for doing so largely revolve around maintaining peace of mind and producing just outcomes.